Association Between Different Risk Factors And Stroke At Emergency Department In Neuro Science Hospital - Abd, Muataz Fairooz (AL-Kindy College Medical Journal, 2019)
Background: Stroke is an acute neurologic injury and represents the 2nd leading cause of mortality worldwide, and also the most leading cause of acquired disability and morbidity in adults.Objective: Effect and association between stroke and risk factors.Type of the study: A retrospective study.Methods: The study conducted on 312 patients in 2016, all data were collected from patients’ files from the emergency unit, which included basic demographic and disease characteristic, co morbid diseases, risk factors, final diagnosis.Results: both previous stroke, ischemic heart disease was strong predictor of new stroke ,and hypertension was major risk factor that associated with new stroke (odd ratio= 13.034, 2.659and 5.684respectively), no significant correlation between sex and stroke in the collected sample despite that female had slightly higher rate of stroke than male, patients with age above 70 years carry the highest risk to present with stroke.Conclusion: The rate of stroke in Iraqi patients still significantly associated with advance age, two major predictor of stroke are associated with stroke previous stroke and ischemic heart disease and hypertension was the major risk factor correlated with new onset stroke, and prevention programs must be implemented on them especially hypertension since it is modifiable risk factor Background: Stroke is an acute neurologic injury and represents the 2nd leading cause of mortality worldwide, and also the most leading cause of acquired disability and morbidity in adults.Objective: Effect and association between stroke and risk factors.Type of the study: A retrospective study.Methods: The study conducted on 312 patients in 2016, all data were collected from patients’ files from the emergency unit, which included basic demographic and disease characteristic, co morbid diseases, risk factors, final diagnosis.Results: both previous stroke, ischemic heart disease was strong predictor of new stroke ,and hypertension was major risk factor that associated with new stroke (odd ratio= 13.034, 2.659and 5.684respectively), no significant correlation between sex and stroke in the collected sample despite that female had slightly higher rate of stroke than male, patients with age above 70 years carry the highest risk to present with stroke.Conclusion: The rate of stroke in Iraqi patients still significantly associated with advance age, two major predictor of stroke are associated with stroke previous stroke and ischemic heart disease and hypertension was the major risk factor correlated with new onset stroke, and prevention programs must be implemented on them especially hypertension since it is modifiable risk factor